Tuturan Ritual Be’eula dalam Upacara Kematian pada Masyarakat Desa Oetutulu Kecamatan Rote Barat Laut Kabupaten Rote Ndao - Rudolof J. Isu; Temy M. E. Ingunau (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2020)
This study aims to describe the meaning and function contained in the Ritual Speech of Be'eula in the death ceremony at the Oetutulu Village Community, North West Rote District, Rote Ndao District. Be'eula's ritual speech is the process of handing over betel nut sites from families who are grieving to parents or traditional elders who have selected the same age as those who have died after the funeral process. Attitudes to maintain cultural traditions, especially beeeula in the community of Oetutulu Village, North West Rote Subdistrict, Rote Ndao District illustrate people's obedience to ancestral heritage. The people of Oetutulu Village, North West Rote Subdistrict, Rote Ndao District are aware that Be'eula Ritual speech has meaning and function that is very important for their lives. The intended meaning and function also describe their existence or identity as a civilized society. The results of the study showed that in the ritual speech of be’eula in the death ceremony that occurred in the community of Oetutulu Village, Rote Barat Laut District, Rote Ndao District contained several meanings. The meanings meant here are (1) Religious Meaning; (2) Meaning of Togetherness; and (3) The Meaning of Affection. While the function in the ritual speech be'eula in Oetutulu Village community, North West Rote District, Rote Ndao Regency, consists of three functions, namely: (1) Poetic Function; (2) Religious functions; and (3) Function of Directive.